CARDINAL BANGGAI FISH Pterapogon kauderni HATCHERY MANAGEMENT AT BALAI PERIKANAN BUDIDAYA LAUT (BPBL) LOMBOK, WEST NUSA TENGGARA: MANAJEMEN PEMBENIHAN IKAN KARDINAL BANGGAI Pterapogon kauderni DI BALAI PERIKANAN BUDIDAYA LAUT (BPBL) LOMBOK, NUSA TENGGARA BARAT - Ramadhani, Dian Eka; Wafi Nurrafa, Nazla; Erlan Hafid Djunaedi, Muhamad; Arif Mulya, Muhammad; Eny Indriastuti, Cecilia (IPB University, 2023)
The Banggai cardinal fish has quite high commercial value as an ornamental fish. There are around 700,000‒900,000 traded cardinal fish per year. The Banggai cardinal hatchery currently needs to be developed. Efforts are being made, namely the development of the production of Banggai cardinal fish seeds by using technology that is easy to apply. The purpose of this study was to gather information on the techniques for seeding cardinal Banggai to produce quality seeds. The Banggai cardinal fish is a type of fish that incubates eggs in its mouth or is called a mouth breeder. The total number of eggs incubated by the mother is 1.520 eggs. The number of eggs that came out of the mother's mouth was 1.115 so the hatching rate (HR) obtained was 76%. The seed survival rate at the end of the observation was 95% with a total revenue of IDR 95.040.000 and a profit of IDR 19.795500.